PENGARUH LINGKUNGAN KELUARGA DAN GAYA BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA KELAS XI IPS MATA PELAJARAN EKONOMI DI SMAN 1 KOTA JAMBI - Saputra, Bayu; Yudha, Redi Indra (SJEE (Scientific Journals of Economic Education), 2021)
Abstract This study aims to determine (1) Knowing the description of the family environment, learning styles, and learning outcomes in the economic subjects of class XI IPS at SMA Negeri 1 Jambi City. (2) Knowing the influence of the family environment on learning outcomes in economic subjects in class XI IPS Negeri 1 Jambi City. (3) Knowing the effect of learning styles on learning outcomes in economic subjects in class XI IPS Negeri 1 Jambi City. 4) Knowing the effect of the family environment and student learning styles on student learning outcomes of class XI IPS on economic subjects at SMA Negeri 1 Jambi City. This research design uses quantitative research methods, with data collection techniques through observation, interviews, and questionnaires. Where the population in this study were 143 students with a sample of 106 students. The research instrument test technique used in this study is the Validity and Reliability Test, while the classical assumption tests used are Quantitative Descriptive Analysis, Normality Test, Homogeneity Test, and Multiple Regression Test. The results showed that: (1) The family environment and learning style were included in the fairly good category with an average TCR (X1) of 77.10%, (X2) 75.36%, and student learning outcomes in economic subjects were obtained. A score of less than 68 was 72 students, while those who scored above 68 were 34 students.(2) There is an influence of the family environment on learning outcomes which can be seen from the tcount value of the family environment variable (X1) of 2,212> 1,658. (3) There is an effect of learning styles on learning outcomes which can be seen from the tcount> ttable that the tcount of learning style variable (X2) is 2.184> 1.658). 4) There is an effect of the family environment and student learning styles on student learning outcomes with a value of 8.892 with a significant value of .000. Thus, a good family environment will have a positive impact on children so that children become enthusiastic in carrying out the learning process, and learning styles are influential enough for each individual to absorb information from outside himself. So, with a family environment and a good learning style it can improve student learning outcomes Keywords: Family Environment, Learning Style, Learning Outcome